Molecular profiling of head and neck squamous cell carcinoma. (28th November 2015) - Feldman, Rebecca; Gatalica, Zoran; Knezetic, Joseph; Reddy, Sandeep; Nathan, Cherie‐Ann; Javadi, Nader; Teknos, Theodoros
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) exhibits high rates of recurrence, and with few approved targeted agents, novel treatments are needed. We analyzed a molecular profiling database for the distribution of biomarkers predictive of chemotherapies and targeted agents. Methods: Seven hundred thirty‐five patients with advanced HNSCC (88 with known human papillomavirus [HPV] status), were profiled using multiple platforms (gene sequencing, gene copy number, and protein expression). Results: Among the entire patient population studied, epidermal growth factor receptor (EGFR) was the protein most often overexpressed (90%), TP53 gene most often mutated (41%), and phosphatidylinositol 3‐kinase (PIK3CA) most often amplified (40%; n  = 5). With the exception of TP53 mutation, other biomarker frequencies were not significantly different among HPV‐positive or HPV‐negative patients. PIK3CA mutations and phosphatase and tensin homolog (PTEN) loss are frequent events, independent of HPV status. The immune response‐modulating programmed cell death 1 (PD1) and programmed cell death ligand 1 (PDL1) axis was active across sites, stages, and HPV status. Conclusion: Molecular profiling utilizing multiple platforms provides a range of therapy options beyond standard of care. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1625–E1638, 2016